(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
In this paper a quarter-vehicle full-scale suspension test rig was designed and manufactured,the suspension is considered semi-active as the electrohydraulic (EH) damper used is fullycontrolled. This gives an indoor-based simulation tool which is important for vehicle testing;.This reduces the cost significantly with accurate results, especially when designing a newsuspension system. The aim of the current work was to build a new quarter-vehicle test rigwith expandable capabilities for diverse design objectives, also may be used for academicpurposes. The control objective was achieved by using dynamic characteristics of theelectrohydraulic (EH) damper to suppress the oscillation of the sprung mass due to roadirregularities. The test rig was constructed using a Genesis G80 (2016) suspension system.Finally, the simulation results demonstrated that the proposed controller used be able toefficiently regulate the chassis vertical oscillation under these irregularities. The experimentalresults for the quarter-car model showed good results between experimental and simulatedresults, where the proportion of conformity about 95%.